GARCÍA-HUIDOBRO, JOAQUÍN, COMUNIDAD: LA PALABRA QUE FALTA, VALENCIA, TIRANT HUMANIDADES, 2020, 285 PP - Menem, Paulina (Prudentia Iuris, 2022)
GARCÍA-HUIDOBRO, JOAQUÍN, COMUNIDAD: LA PALABRA QUE FALTA, VALENCIA, TIRANT HUMANIDADES, 2020, 285 PP